Neighborhood Effects on Tree Mortality Depend on Life Stage of Neighbors - He, Yi; Liu, Heming; Yang, Qingsong; Cao, Ye; Yin, Huimin; Zhou, Zhengkang; Yu, Qiuwu; Wang, Xihua (Frontiers in Plant Science, 2022)
Neighborhood effects are a crucial ecological processes that allow species to coexist in a forest. Conspecific and heterospecific neighbors, as major group classifications, affect tree mortality through various mechanisms associated with neighbor life stages. However, the influence of neighbor life stages on neighborhood effects and by what mechanisms remains a knowledge gap. Here we censused the mortality of 82,202 trees belonging to 30 species in a 20-ha subtropical forest and classified their neighbors into the following life stages: earlier, same and later. Next, we implemented generalized linear mixed models to estimate the effect of neighbors at different life stages on tree mortality. Our results showed that conspecific later stage neighbors had a positive effect on tree mortality overall, while conspecific earlier stage neighbors had a negative effect on tree mortality. Furthermore, these opposing effects appear to offset each other so that the overall effect of conspecific neighbors on tree mortality is weakened. In contrast, heterospecific neighbors had a decreasing effect on tree mortality overall. These effects are consistent with those of later stage heterospecific neighbors. Our findings demonstrate that neighbors strongly impact tree mortality, and their specific effects are closely related to neighbor life stages. Further, any single effect from one neighbor life stage may disturb or dominate the total effects of the neighbors. Therefore, the neighbors must be divided into different life stages to best explain the neighborhood effect on forest dynamics.